Masculinidades e saúde reprodutiva : a experiência da vasectomia - Santos, Ana Elizabeth Lole dos (2006)
This thesis is part of the research area of Social Protection and Interventive Process of the Post-Graduation Program of Social Policy/UFF. It analyses gender relations in practices and social representations that organize and gendercize some activities of policies or programs dealing with reproductive health. Focusing on masculinities, it displays observations centred on requests of vasectomy revealed in classes of health education, in the period from 2001 up to 2003, in joint sessions of men and women seeking to assure their rights to voluntary sterilization, one of the activities of family planning of the Universitary Hospital Antonio Pedro/UFF, in Niteroi, during this period. It distinguishes conceptual references that have been feminizing the Integral Women´s Health Assistance Program (PAISM), where those activities were being held, and bring up prejudice actions against men, in a qualitative approach based on oral history. Interviews made with professionals have increased the number of elements of evaluation of programs being developed on reproductive health in matters of reproductive and sexual rights. These interviews made with vasectomized men brought new information on personal and collective experience of masculine sterilization, confirming that the access to that kind of rights are well associated to changing behavior and new masculine and feminine sociabilities. It emphasizes the problems of previous researches and the gaps of knowledge regarding this issue, while showing the importance of making deeper studies.